Refining the Mouse Subtotal Nephrectomy in Male 129S2/SV Mice for Consistent Modeling of Progressive Kidney Disease With Renal Inflammation and Cardiac Dysfunction - O’Sullivan, James; Finnie, Sarah Louise; Teenan, Oliver; Cairns, Carolynn; Boyd, Andrew; Bailey, Matthew A.; Thomson, Adrian; Hughes, Jeremy; Bénézech, Cécile; Conway, Bryan Ronald; Denby, Laura (Frontiers in Physiology, 2019)
Chronic kidney disease (CKD) is prevalent worldwide and is associated with significant co-morbidities including cardiovascular disease. Traditionally, the subtotal nephrectomy (remnant kidney) experimental model has been performed in rats to model progressive renal disease. The model experimentally mimics CKD by reducing nephron number, resulting in renal insufficiency. Presently, there is a lack of translation of pre-clinical findings into successful clinical results. The pre-clinical nephrology field would benefit from reproducible progressive renal disease models in mice in order to avail of more widely available transgenics and experimental tools to dissect mechanisms of disease. Here we evaluate if a simplified single step subtotal nephrectomy (STNx) model performed in the 129S2/SV mouse can recapitulate the renal and cardiac changes observed in patients with CKD in a reproducible and robust way. The single step STNx surgery was well tolerated and resulted in clinically relevant outcomes including hypertension, increased urinary albumin:creatinine ratio, and significantly increased serum creatinine, phosphate and BUN. STNx mice developed significant left ventricular hypertrophy without reduced ejection fraction or cardiac fibrosis. Analysis of intra-renal inflammation revealed persistent recruitment of Ly6chi monocytes transitioning to pro-fibrotic inflammatory macrophages in STNx kidneys. Unlike 129S2/SV mice, C57BL/6 mice exhibited renal fibrosis without proteinuria, renal dysfunction renal disease or cardiac pathology. Therefore, the 129S2/SV genetic background is susceptible to induction of progressive proteinuric renal disease and cardiac hypertrophy using our refined, single-step flank STNx method. This reproducible model could be used to study the systemic pathophysiological changes induced by CKD in the kidney and the heart, intra-renal inflammation and for testing new therapies for CKD.